2020
DOI: 10.3390/ijms21176171
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Effect of Pyridine-N-Position on Structural Properties of Cu-Based Low-Dimensional Coordination Frameworks

Abstract: Metal-organic assemblies have received significant attention for catalytic and other applications, including gas and energy storage, due to their porosity and thermal/chemical stability. Here, we report the synthesis and physicochemical characterization of three metallosupramolecular assemblies consisting of isomeric ambidentate pyridyl-β-diketonate ligands L1–L3 and Cu(II) metal ions. It has been demonstrated that the topology and dimensionality of generated supramolecular aggregates depend on the location of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…14,18−28 The resulting structures include helicates, 29,30 tetrahedra, 31−33 and interlocked assemblies, 23,34 as well as stimuli-responsive 24 and exceptionally porous polymeric systems. 35,36 Here, we present an investigation into the tritopic βdiketone ligand H 3 L and its interaction with both copper(II) and palladium(II) ions. The coordination of similar ligands with iron(III) and gallium(III) by Saalfrank and Raymond produced charge-neutral [M 4 L 4 ] tetrahedral and [M 6 L 6 ] trigonal antiprismatic assemblies, 37,38 however, no investigations into the use of divalent metals have been previously reported.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,18−28 The resulting structures include helicates, 29,30 tetrahedra, 31−33 and interlocked assemblies, 23,34 as well as stimuli-responsive 24 and exceptionally porous polymeric systems. 35,36 Here, we present an investigation into the tritopic βdiketone ligand H 3 L and its interaction with both copper(II) and palladium(II) ions. The coordination of similar ligands with iron(III) and gallium(III) by Saalfrank and Raymond produced charge-neutral [M 4 L 4 ] tetrahedral and [M 6 L 6 ] trigonal antiprismatic assemblies, 37,38 however, no investigations into the use of divalent metals have been previously reported.…”
Section: ■ Introductionmentioning
confidence: 99%
“…They have been shown, for example, to display a wide range of guest-binding, catalysis, and storage/separation uses. , The design of the building blocks that are programmed to assemble into these architectures plays a crucial role in determining both the form and function of the resulting metallosupramolecular complexes. It has been shown that ligands incorporating multiple β-diketone groups can be reacted with certain metal ions to form a series of metallosupramolecular structures with a significant degree of predictability. , The resulting structures include helicates, , tetrahedra, and interlocked assemblies, , as well as stimuli-responsive and exceptionally porous polymeric systems. , …”
Section: Introductionmentioning
confidence: 99%
“…17,18 In most cases, they act as O,O-chelates or as simple N-donors through the pyridine ring, but other coordination modes can be achieved. 19,20 Due to this structural variety they have found a number of applications in the construction of sophisticated coordination assemblies, including complex compounds, [21][22][23][24] macrocycles, 14 multimetallic polymers, 20,25,26 metal-organic frameworks (MOFs) 27,28 and metallocages. [29][30][31] Although a number of reports on metallosupramolecular assemblies based on pyridyl-β-diketonate-derived ligands are available in the literature, we focused on an unexplored aspect, namely the switchable nature of species with such units as well as conducting studies on the application potential of new heterometallic aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…Arthur Hantzsch later synthesized (1881) pyridine compounds by the synthesis that bears his name, through a multicomponent reaction, starting from a β-ketoester, an aldehyde and ammonia [ 2 , 3 ]. An important role of pyridine is that it is used as an organic solvent or as ligand for coordination complexes [ 4 , 5 , 6 , 7 , 8 ]. The pyridine nucleus is found in many natural products, such as vitamins, alkaloids and coenzymes, as well as in many drugs ( Figure 1 ) and pesticides [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recent literature mentions various series of compounds containing the pyridine nucleus, as a unique heterocycle, and with other heterocycles or fused with other heterocycles, which have remarkable antibacterial, antifungal and antiviral properties [ 1 , 9 , 10 , 11 , 12 , 13 ]. The presence of an additional heterocycle compared to the pyridine one in the bioactive molecule proved to be beneficial in the sense that it intensified the therapeutic properties of the antimicrobial and antiviral ones, and also widened their range [ 3 , 4 , 5 , 6 , 7 , 8 ]. Moreover, the presence of certain organic groups, such as amino, hydroxy, methoxy, sulfamide, hydrazide, etc., increase the biological activities of the compounds, as noted in the literature.…”
Section: Introductionmentioning
confidence: 99%